2016
DOI: 10.1097/dcr.0000000000000510
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Rising Grades of Internal Rectal Intussusception on Fecal Continence and Symptoms of Constipation

Abstract: Increasing grades of rectal intussusception are associated with increasing fecal incontinence but not constipation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 32 publications
3
31
0
1
Order By: Relevance
“…[53][54][55] A greater Oxford rectal prolapse grade 56 is associated with increased fecal incontinence severity. 57 The subgroup analysis indicated that anal canal hyposensitivity was associated with more severe incontinence scores in women.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…[53][54][55] A greater Oxford rectal prolapse grade 56 is associated with increased fecal incontinence severity. 57 The subgroup analysis indicated that anal canal hyposensitivity was associated with more severe incontinence scores in women.…”
Section: Discussionmentioning
confidence: 97%
“…While internal anal sphincter atrophy and degeneration is increasingly recognized to be of pathological importance, increased IAS thickness is observed in rectal intussusception and/or rectal prolapse, which can contribute to fecal incontinence 53‐55 . A greater Oxford rectal prolapse grade 56 is associated with increased fecal incontinence severity 57 …”
Section: Discussionmentioning
confidence: 99%
“…Dvorkin examined 896 proctograms and found anorectal pain and prolapse were predictive of intussusception on proctography but there were no symptoms which distinguished between obstructing and nonobstructing intussusception on proctography [7]. Intussusception has also been shown to play a role in faecal incontinence [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…The mean or median scores in those patients with and without certain features obstructing and nonobstructing intussusception on proctography [7].Intussusception has also been shown to play a role in faecal incontinence [8,9].…”
Section: Ta B L Ementioning
confidence: 99%
See 1 more Smart Citation